Development of molecular dynamics solver - Koh, Angeline Yan Yan. (2009)
Molecular Dynamics simulation is a computer simulation in which particles are allowed to interact for a period of time. It is a specialized discipline of molecular modeling and computer simulation with ergodic hypothesis as the main justification of Molecular Dynamics. In this project, a Molecular Dynamics solver is developed using C program. This solver helps one to gain more insights regarding the properties of many-particle systems, by measuring quantities like energy of system, pressure and radial distribution function. These quantities are compared with literature, so as to determine if the solver is giving the right result. From the results, it is seen that there is a little discrepancy from literature. This difference can be kept to the minimal by running the simulation for longer times and having smaller time steps. With approximately the same result as literature, this Molecular Dynamics solver is developed in its initial stage, more improvements are needed to ensure a well-developed solver.